Resurfacing the disappeared the author in fish-hair woman by Merlinda Bobis - Santos, Jaimee Faith J. (2017)
Access online through this link: https://www.plarideljournal.org/article/resurfacing-disappeared-author-fish-hair-woman-merlinda-bobis
Keywords: Bobis, Merlinda; Literary criticism; Fiction